Students’ Perception Toward Active Learning Method in English Learning - Sari, Indah (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This study aimed to analyse students' perceptions of active learning methods in English language learning. Active learning methods, which emphasize students' active participation, are expected to improve motivation and learning outcomes in English language acquisition. The study was conducted by using a qualitative approach through surveys to 30 students if second semester in System of Technology and Information study program at Institut Teknologi Sawit Indonesia ((ITSI) North Sumatera, Indonesia. The results showed that most students had a positive view of the method, feeling improved communication skills and understanding of the material. However, some challenges such as difficulties in collaboration and adaptation to the new method were also identified. The findings provide insights for curriculum developers and teachers to optimize the application of active learning methods, to increase the effectiveness of English language learning in higher education